The Effect of Addition on Pumice and Fiber on Compressive and Fluxural Strength Precast Lightweight Concrete: - - Indrayani Indrayani; Andi Herius; Arfan Hasan; Ahmad Mirza (Science and Technology Indonesia, 2020)
Most of the construction uses concrete as the main building material because concrete has many advantages compared to other materials. Concrete has a high enough weight, various attempts were made to reduce the weight of the concrete for example using lightweight aggregates or concrete made without sand or concrete made hollow Innovations in the development of precast lightweight concrete are urgently needed at this time to support the development of development that is being carried out by the government. From the studies that have been carried out on lightweight concrete and fiber concrete, this research will develop the results of previous studies, namely by combining lightweight concrete and fiber concrete to obtain precast lightweight concrete. This research was conducted to find out how much influence the use of pumice and and fiber on compressive strength and flexural strength of precast lightweight concrete. Variations in the addition of a mixture of pumice with aggregate are divided into 4 comparisons, namely 0: 100, 20: 80, 40: 60, 60: 40, where each mixture is added 0.1% fiber from the volume of concrete, then printed in cube and beam molds. Compressive tests were carried out on the cube and flexural tests were carried out on beams. From the test results was obtained that the addition of pumice to the concrete mixture can cause a decrease in compressive strength of the concrete from 202 kg/cm2 to 129 kg/cm2 whereas with the addition of fiber there is an increase in flexural strength is 24.48 kg/cm2. The specific gravity obtained is 1.664 gr/cm3 so this concrete can be classified into lightweight concrete.